Responsible and safe innovation in education: an iGEM showcase - Britte Bouchaut; Lotte Asveld (Journal of Responsible Innovation, 2025)
This paper showcases a project involved in the international Genetically Engineered Machines (iGEM) competition – a competition dedicated to the advancement of synthetic biology – executed at Delft University of Technology, the Netherlands. Through this case, we illustrate how Value Sensitive Design (VSD) and Safe by Design (SbD) are embedded in education associated with iGEM to arrive at a safe and responsible project design by integrating values and, particularly, the value of safety. As particularly SbD is still quite generally described in literature, we aim to make SbD more tangible to peers, and to inspire other iGEM teams and educators. In addition, we reflect on VSD and SbD in the context of Responsible Research and Innovation and provide guidelines for other iGEM projects to implement VSD and SbD approaches in their designs. To conclude, we explore if, and how SbD and iGEM projects could function as anticipatory governance tools for synthetic biology.